Factors affecting perceived effectiveness of COVID-19 prevention measures among filipinos during enhanced community quarantine in luzon, philippines: Integrating protection motivation theory and extended theory of planned behavior (2020)
Objective: The current study integrated Protection Motivation Theory (PMT) and extended Theory of Planned Behavior (TPB) to evaluate factors affecting the perceived effectiveness of COVID-19 prevention measures among Filipinos during Enhanced Community Quarantine (ECQ) in Luzon, Philippines. Methods: A total of 649 Filipinos answered an online questionnaire, which contained 63 questions. Structural Equation Modeling (SEM) was utilized to derive the causal relationships of the latent variables construct. Results: SEM showed that understanding of COVID-19 had significant direct effects on perceived vulnerability and perceived severity. Also, perceived vulnerability and perceived severity had significant indirect effects on intention to follow. Intention to follow had significant direct effects on actual behavior and adapted behavior, which subsequently led to perceived effectiveness. Of note, an understanding of COVID-19 was found to have a significant indirect effect on perceived effectiveness. Conclusions: The current study is one of the first studies to analyze factors affecting the perceived effectiveness of COVID-19 prevention measures during the global pandemic. It is proposed that the integrated PMT and extended TPB of this study can be applied and extended to evaluate the perceived effectiveness of COVID-19 measures in other countries that are currently dealing with COVID-19 pandemic. © 2020 The Author(s). Published by Elsevier Ltd on behalf of International Society for Infectious Diseases.